Use of digital tools to improve the learning of differential calculus competence in engineering students (LACCEI, 2024)
The objective of this study was to demonstrate the improvement generated by the use of digital tools in the learning of differential calculus competence in students of the school of industrial engineering. Its approach was quantitative and was developed considering a quasi-experimental design, it was applied to 80 students of calculus I, experimental group 40 students and control group 40 students. A written test was administered individually using the virtual tool WirisQuizzes of Blackboard, the instrument was validated using the expert judgment technique, and by using the Spearman-Brown coefficient in the test of the two halves it reached a reliability of 0.941. The results showed that the use of digital tools contributed to the improvement of competences in differential calculus in the students, which was reflected in the results of the post-test in the experimental group where 47.5% (19 students) were at the satisfactory level, which when compared with the results obtained in the post-test of the control group, it was verified that this reached only 7.5% (3 students). When the general and specific hypotheses were tested, these presented an asymptotic significance p= 0.000, so the null hypothesis was rejected.